Ambiente para especificação de aplicações multimídia com suporte de qualidade de serviço - Thereza, Wesley Barbosa (Universidade Federal de São Carlos, 2004)
This work describes an environment for specification of distributed multimedia applications with demanded Quality of Service (QoS) detailing. The description of the application is made in a hierarchic way, in the user, application and resource level, adding the demanded QoS parameters and the adaptation rules to be applied for the Quality of Service monitoring/ (re)negotiation. These rules and QoS parameters will be responsible for the activation of the system adaptation to guarantee its execution in compliance with the Quality of Service negotiated in the specification. After the specification phase of the distributed multimedia system, the environment generates the documentation in a specification language of system with QoS detailing and its adaptation/ (re)negotiation forms. This documentation feeds NIST Net emulator, allowing that the results can be analyzed by the verification of the multimedia system behavior and the emulated system.
Keywords: Sistemas multimídia; Qualidade de serviço; Linguagem de marcação; HQML; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO